Revisited maxillary sinus pneumatization narrative of observation in Al-Madinah Al-Munawwarah, Saudi Arabia: A retrospective cross-sectional study - Elsayed, Shadia A. (Saudi Dent J, 2019)
OBJECTIVES: Maxillary sinus pneumatization (MSP), is linked worldwide to number of factors. MSP measurements and assessment alongside potential correlates in Al-Madinah Al-Munawwarah, Saudi Arabia (SA) awaits identification. MATERIALS AND METHODS: A retrospective cross-sectional study was conducted at Taibah University Dental-College and Hospital, Al-Madinah Al-Munawwarah; SA. The analysis included 700 female patients digital Orthopantomogram (OPG), of which 535 (76%) OPGs were usable. MSP was established according to the distance between the maxillary sinus floor and posterior teeth apices number 15, 16, 17, 18, 25, 26, 27 and 28. MSP categorized as followed: Sever MSP (Category I), Moderate MSP (Category II) and No MSP/normal (Category III). Descriptive statistics, and inferential analysis were carried out. RESULTS: Mean age of the patients was 30.11 (±10.26) and 290 (54.5%) were Saudi nationals. Severe pneumatization (category I) was prominent in the right and left first and second molars, 16, 26, 17, 27 (66%, 64%, 63% and 62%, respectively). A statistically significant difference (P < 0.0005) was observed between pneumatization categories in all sites. Furthermore, the impact of young age on levels of MSP was statistically significant (P < 0.05) on most teeth. However, nationality was non-significantly (P > 0.05) associated with MSP levels. CONCLUSION: High percentages of female patients showed bilateral sever MSP in the upper molar area, specifically, young age group. CLINICAL SIGNIFICANCE: The oro-antral communication during extraction and surgical cases of female patients’ maxillary teeth is possible. This should be considered during dentists’ daily practice in this geographic area of SA.